Pelindungan Hukum Terhadap Konsumen dan Akuntabilitas Pelaku Usaha Produk Skincare Etiket Biru di Indonesia - Mutiara Hikmah; Nooraini Dyah Rahmawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The increasing trend in skincare usage, particularly whitening products, has led many business actors to market their products extensively without regard for legal compliance. One notable issue is the circulation of blue-label skincare products, which should only be provided with a doctor's prescription. The research employs a normative juridical method with a qualitative approach, utilizing interviews and literature study. The findings reveal that legal protection for consumers in the use of blue-label skincare products remains suboptimal. These products often contain active ingredients such as corticosteroids or antibiotics, which should only be used under a doctor's prescription and supervision. However, in practice, many business actors continue to sell them freely via online marketplaces and social media platforms. This not only violates BPOM regulations and health laws but also poses a direct threat to consumer safety. Furthermore, business accountability is still lacking, as evidenced by the insufficient transparency regarding product content, usage instructions, and distribution permits.